ABOUT THE PROBLEM OF INCOMPLETE CALCULATION OF TAXES BY TAX AUTHORITIES IN THE COURSE OF TAX CONTROL - A. V. Ilin (Publishing House of the State University of Management, 2020)
The subject of the study is the state of tax control as a significant institution of the tax system in Russia. An analysis of changes in legislation on taxes and fees, literature and taxation practices has pointed to the urgency of the problem of incomplete taxation by tax authorities during tax control. The purpose of the article is to study the completeness of tax calculation by tax authorities during tax control and justify the rejection of a model for compensating low tax risks for offenders by increasing the tax burden for law-abiding taxpayers. The insufficiency of desk tax audits after the introduction into the tax system of Russia of the limits on the exercise of taxpayer rights to calculate the tax base and (or) the amount of tax has been criticized in the article. It has been indicated to the possibility of incomplete calculation of taxes by the tax authority during tax control as a result of a conspiracy with the taxpayer. It has been concluded about the importance of monitoring the completeness of tax calculation by tax authorities, the need to increase the number of tax audits and abandoning the model of compensating low tax risks for offenders by increasing the tax burden for law-abiding taxpayers.